2019
DOI: 10.1039/c9ta00550a
|View full text |Cite
|
Sign up to set email alerts
|

Design of doped cesium lead halide perovskite as a photo-catalytic CO2 reduction catalyst

Abstract: The stronger absorption of intermediate molecules, the lower free energy barrier, and the smaller band gap as well as the charge accommodation mechanism compared with the intrinsic case reveal that Co-doped CsPbBr3 could be a promising candidate for CO2 reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 60 publications
1
76
0
Order By: Relevance
“…The group of Xu explored the doped CsPbBr 3 perovskite for photocatalytic CO 2 reduction to CH 4 based on DFT calculations . The results demonstrated that doped CsPbBr 3 showed improved photoactivity and selectivity compared with that of pristine CsPbBr 3 .…”
Section: Engineering Mhps For Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…The group of Xu explored the doped CsPbBr 3 perovskite for photocatalytic CO 2 reduction to CH 4 based on DFT calculations . The results demonstrated that doped CsPbBr 3 showed improved photoactivity and selectivity compared with that of pristine CsPbBr 3 .…”
Section: Engineering Mhps For Photocatalysismentioning
confidence: 99%
“…The optimum MAPbI 3 @PCN‐221(Fe 0.2 ) sample exhibited the highest yield of 19.5 μmol g −1 h −1 for photocatalytic CO 2 reduction, with CH 4 /CO=2/1. The selectivity of CH 4 formation was highly dependent on the content of Fe catalytic sites, which was consist with calculation results reported by Tang et al …”
Section: Engineering Mhps For Photocatalysismentioning
confidence: 99%
“…Tang et al used density functional theory calculations to elucidate the mechanisms of the reduction of CO 2 to CH 4 using CsPbBr 3 and doped CsPbBr 3 as catalysts. 80 CO 2 was reduced to many intermediates, such as HCOO*, HCO*OH, CO*, and HCO*, before being converted to CH 4 . It can be observed that in the case of Fe-CsPbBr 3 and Co-CsPbBr 3 catalysts, the free energy of intermediates was much lower than in pristine CsPbBr 3 case, as shown in Fig.…”
Section: Hp Photocatalysis Co 2 Reduction Reactionmentioning
confidence: 99%
“…The change in Gibbs free energy (ΔG) of the rate-determining step is listed for each case. Reproduced with permission 80. Copyright 2019.…”
mentioning
confidence: 99%
“…These dopants into halide perovskites have shown various optical and electrical properties changes. [45][46][47][48][49][50][51][52][53] The dopants in halide perovskites usually can control over the optoelectronic properties of the material, such as crystal growth, structural stability and light emitting and light absorption. And the same element doping may cause changes in more than one property.…”
Section: Introductionmentioning
confidence: 99%